Prenatal Diagnosis of Congenital Heart Disease IN A Fetus with A 8p23.1 Interstitial Deletion - Simão, Laurentino (2022)
Abstract publicado em:Medicine (Baltimore). 2021 Jan 29;100(4):e23585. doi: 10.1097/MD.0000000000023585